Endometrial carcinoma review : a 10-year Hospital Universiti Sains Malaysia experience (January 2002-December 2011) - Kamarudin, Mohd Irwan (2016)
Objective: This study was conducted to determine the prevalence, and to evaluate the response of all treatment modalities, and to determine the incidence of recurrence, and to determine the survival rate of endometrial carcinoma cases that was managed in Hospital University Sains Malaysia from January 2002 until December 2011. Methodology: This is a retrospective study, which conducted by reviewing the patients‟ medical records with diagnosis of “endometrial cancer, endometrial carcinoma, or uterine cancer”. Relevant information was obtained, recorded then analysed using descriptive statistics. The one sample t test was used to determine the significant mean for some of the associated factors. For survival analysis, simple univariate and multivariate Cox regression model was used. Results: A total of 56 cases were included in this study. Majority of the patients were Malays (89.3%), and Chinese (8.9%). The factors that associated incidence of endometrial carcinoma were postmenopausal age with peak incidence was in age group of 50-55 years, mean age 54.3 years (SD 11.77, p = 0.036), nulliparity and low parity (mean 2.75, SD 2.63, p = < 0.001), increase body mass index (BMI) with mean BMI 27.2 kg/m2 (SD 5.43, p = 0.003) and those with underlying hypertension (53.6%) and diabetes mellitus (21.4%). Almost all patients were symptomatic at time of presentation (96.4%) with the main presenting symptoms of per vaginal bleeding in 91.1% and abdominal pain in 19.6% of patients. However, majority of the patients (55.4%) did not have any remarkable physical finding when they presented. For the rest of them, the commonest physical finding was the presence of abdominal mass (39.3%). Ultrasound was the main imaging modality. The main sonographic features of patients with endometrial carcinoma were abnormal thickened endometrium equal or greater than 5 mm (85.7%) which were common in the postmenopausal patients (46.4%) and enlarged uterus (48.2%). The preferred first line of diagnostic test was pipelle sampling (42.9%), followed by hysteroscopic tissue biopsy (28.6%). When the disease was staged, majority of patient were in stage I (67.9%). For other stages, 8.9% of patients were in stage II, 19.7% were in stage III and 3.6% in stage IV. The commonest histological type was the endometrioid adenocarcinoma with its subtypes (87.5%). The other types of histology were less common, with serous cell type in 3.6% of cases, clear cell type in 3.6%, mixed adenocarcinoma in 3.6% of cases and undifferentiated type in 1.8%. With regards to histological grades, many tumours were grade 1 (41.1%) and grade 2 (39.3%) and only 19.6% were grade 3 tumours. The predominant histological type of tumours with grade 1 and grade 2 were endometrioid adenocarcinoma, whereas for the grade 3 tumours were usually the other carcinoma subtype (serous cell, clear cell, mixed adenocarcinoma, and undifferentiated). Theendometrioid adenocarcinoma types of tumours were commonly occurred in early stages and in patient at age below 60. From the aspect of treatment, all patients had undergone surgery through the course of treatment. For modalities of treatments, majority had surgery followed with adjuvant radiotherapy (46.4%), while other 39.3% of patients had undergone surgery only. For the types of surgery, the type of surgery performed on most number of patients was extrafacial hysterectomy and bilateral salphingo-oopherectomy (BSO) (46.4%), followed by simple hysterectomy and BSO (41.1%). Despite appropriate treatment, a small number of the patients still developed recurrence, and later death. 75.0% of patients were disease free after 24 months, while the rest of 25.0% developed recurrence within less than 24 months, with the most of the patients (12.5%) developed persistence disease within less than 6 months following treatment. 80.4% of patients were still alive after 24 months following treatment, while other 19.6% of patients died in less than 24 months, with the most death (12.5%) occurred in less than 6 months. The significant prognostic factor were stage (stage III, p = 0.003, adjusted HR 26.243) and histological tumour grade (p = 0.015, adjusted HR 10.887). The 2-years survival rate was 97.4% for stage I, 60.0% for stage II, 36.4% for stage III, and 50.0% for stage IV. Conclusions: Despite the inability to come up with survival rate of 5 years due to limitation of the study, the survival rates at 2 years had managed to show the strong prognostic influence of stage and grade.